Investigation the Effect of Die Angle and Punch Speed in ECAP Process on Improvement the Mechanical Properties of AA7075 - Walla Fareed Jaber; Prof. Dr. Adnan N. Abood; Prof. Dr. Ali H. Saleh (Genius Journals, 2022)
In this study, the possibility of improving the mechanical properties of aluminum alloy o 7075 through the ECAP process was investigated. Three angles are 90o , 105o and 120 for ECAP die are adopted for samples of the alloy with a square cross-sectional area of 10x10mm and the two forming speeds are 5mm/min and 10mm/min. A die was made of tool steel and punches made of high speed steel were used. Through the . The results of o implementation of the experiments, the sample failed with the angle 90 the process showed that the maximum load increases with the decrease in the angle and and it did o that the effect of speed in the first pass (rout A) was clear with the angle 120 . While in the second pass (rout B) not appear to have a clear effect with the angle 105o for the same samples the maximum load increased for all samples and the effect of speed appeared with the two angles. For the purpose of evaluating the improvement in mechanical properties, a compression test was performed on the successful samples, as well as a micro-hardness test and microscopy test. The results showed that the hardness of the alloy was improved through the ECAP process for all angles and speeds used, and the yield stress of the alloy was also significantly improved compared to the base metal due to refining and rearranging of the metal grains. Rout B was carried out for four at two speeds for each angle. The results of the o samples for angles 105o and 120 micro-hardness and yield stress test showed more improvement due to the increase of grain refining in the second pass
Keywords: ECAP process; AA7075; Forming; properties